THE ROLE AND IMPORTANCE OF AUTOMATIC SUBTITLE IN THE PRESENTATION OF VIDEO INFORMATION (Universal International Scientific Journal, 2026)
This thesis analyzes the problem of automatic subtitle generation for video contentwithin the field of computational linguistics. In the digital media environment, the leading role of videocontent in information dissemination has significantly increased the demand for automatic subtitlingtechnologies. The study examines automatic speech recognition (ASR), natural language processing(NLP), and text-to-visual adaptation processes as an integrated system. Based on statistical data, theaudience consuming information through video is analyzed, and the social and educational significanceof automatic subtitles is substantiated
Keywords: computational linguistics; automatic subtitle; ASR